Entrepreneurial place leadership : negotiating the entrepreneurial landscape - Newbery, Robert; Baranchenko, Yevhen; Bell, Colin (Contemporary issues in entrepreneurship research, 2022)
A place-led perspective of entrepreneurial development is becoming increasingly important, given narratives around entrepreneurial ecosystems, contexts, and the design of entrepreneurial institutions. In a world where we recognise entrepreneurial means, ends and values in terms of locations with meaning, this latest volume in Contemporary Issues in Entrepreneurship Research explores the phenomenon of Entrepreneurial Place Leadership. Defining Entrepreneurial Place Leadership in terms of how locations with entrepreneurial meaning are created, maintained, exploited, and amplified to generate future value, this edited collection considers how entrepreneurs lead in a complex entrepreneurial landscape. Leading international scholars act as guides through a heterogeneous landscape of individual dwellings, communities, and planned settlements. Topics include: an exploration of entrepreneurial responsibility to place in rural Nova Scotia; an analysis of culture in Entrepreneurial Support Organisations in Spain; a discussion of entrepreneurial implementation of policy in Italy; and the introduction of a tool for managing a complex solution ecosystem in Australia. Each chapter reflects upon the contribution of the author's research to academic theory and makes policy and practice recommendations - as such this book is a useful resource for academics, students, and entrepreneurial place leaders. Contemporary Issues in Entrepreneurship Research is an official book series of the Institute for Small Business and Entrepreneurship (ISBE). Each volume is designed around a specific theme of importance to the entrepreneurship and small business community with articles collectively exploring and developing theory and practice in the field.